Answered

At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve the following quadratic function by using the quadratic formula: x^2 +
2x - 1 = 2 *


Sagot :

Answer:

x = 1 or x = -3

Step-by-step explanation:

[tex]ax^{2}[/tex] + bx + c = 0

x = [tex]\frac{-b±\sqrt{b^{2}-4ac } }{2a\\}[/tex]

as [tex]x^{2}[/tex] + 2x - 1 = 2 ⇔  [tex]x^{2}[/tex] + 2x - 3 = 0, its solution is

x = [tex]\frac{-2±\sqrt{2^{2}-4 *1*(-3)} }{2*1}[/tex]

=  [tex]\frac{-2±\sqrt{4+12} }{2}[/tex] =  [tex]\frac{-2±\sqrt{16} }{2}[/tex] =  [tex]\frac{-2±\ 4 }{2}[/tex]

therefore, x = 1 or x = -3

hope this helps! :D

have a miraculous day, and brainliest is immensely appreciated!! <3